1989
DOI: 10.1055/s-2007-1012957
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Observation of Hepatic Lobe Atrophy

Abstract: From the standpoint of diagnostic laparoscopy, the frequency and etiological aspect of atrophy of a lobe of the liver was studied. The frequency of hepatic lobe atrophy was 5.3% among 1,208 laparoscopy cases at our department. Lobe atrophy of the liver can be seen not only in congenital anomaly, atrophic cirrhosis and malformation, as described in the OMED database of digestive endoscopy, but also in some other kinds of liver diseases including chronic hepatitis, idiopathic portal hypertension, primary biliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
1
2
Order By: Relevance
“…7 cases, 4 showed atrophy of the right lobe, and 3 showed right-and/or quadrate lobe atrophy. They reported that half of the IPH cases showed hepatic lobar atrophy, but with the exception of report by Watanabe et al, 18 severe atrophy of the right lobe as seen in our case has rarely been reported. [19][20][21] A search of Medline and Medical Central Journals, a local journal database, for 1984-1999, revealed only three cases of a similar condition, all of which showed atrophy occurring predominantly in the right lobe.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…7 cases, 4 showed atrophy of the right lobe, and 3 showed right-and/or quadrate lobe atrophy. They reported that half of the IPH cases showed hepatic lobar atrophy, but with the exception of report by Watanabe et al, 18 severe atrophy of the right lobe as seen in our case has rarely been reported. [19][20][21] A search of Medline and Medical Central Journals, a local journal database, for 1984-1999, revealed only three cases of a similar condition, all of which showed atrophy occurring predominantly in the right lobe.…”
Section: Discussioncontrasting
confidence: 65%
“…[14][15][16][17] As reported by Watanabe et al concerning hepatic lobar atrophy observed on laparoscopy, the incidence of atrophy was 64 cases out of a total of 1208 cases (5.3%), and 7 out of 64 cases (10%) were complicated by IPH. 18 Of those 70 M NAKANO ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Of those 7 cases, 4 showed atrophy of the right lobe, and 3 showed right‐ and/or quadrate lobe atrophy. They reported that half of the IPH cases showed hepatic lobar atrophy, but with the exception of report by Watanabe et al , 18 severe atrophy of the right lobe as seen in our case has rarely been reported 19–21…”
Section: Discussioncontrasting
confidence: 63%